Application of coconut paper motor speed control technology for increasing coconut liquid organic fertilizer productivity - Rinasa Agistya Anugrah; Iswanto Suwarno; Genesiska Genesiska; Muhammad Ahmad Baballe; Irfan Ahmad; Erwin L. Rimban; Mohammad Aljanabi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
The potential that exists in Kadigunung Hamlet, Hargomulyo Village, Kokap District, Kulon Progo Regency, D.I Province. Yogyakarta is where 90% of agricultural land is planted with coconut trees. The livelihoods of its residents are farmers and coconut sugar grinders. However, a lot of coconut husks are not used and are just piled up in people's yards until they become mountains. This results in an increase in unused coconut coir waste. In this hamlet, there are two farmer groups, namely the Forest Farmers Group (Poktan) Tani Makmur and the Women Farmers Group Sedyorukun. Currently, this farmer group in Kadigunung Hamlet has been active in producing POC from coconut fiber as raw material. However, they still find it difficult to peel the coco coir (separating the coir from the coconut shell) in order to get the coco coir that has been separated with large productivity. In addition, residents have not been able to package the POC products in good packaging with trademark labels, which are expected to be commercialized in general. In fact, if residents are able to produce POC products with good packaging and brand labels, residents can sell them in general in the market and can increase the economic income of residents, especially farmer groups in Kadigunung Hamlet. This Community Partnership Service aims to provide solutions to the residents of Kadigunung Hamlet, especially farmer groups by donating appropriate technology tools in the form of a Coconut Coir Peeling Machine that is able to simplify and increase the productivity of processing unused coconut coir waste into products of higher use value, namely to become ready-to-use POCs. used and can be marketed in general. This service program also develops the Kadigunung Hamlet area into an area that can care about the environment with the ability of residents to process waste (waste) independently so as to increase community environmental insight. The output of this Special Scheme Community Partnership Service (PKM) includes appropriate technology products in the form of a Coconut Coir Peeler Machine, POC Processing Module from coconut coir raw materials as well as POC packaging and trademark labeling, Proceedings of the ISBN Community Service national seminar or articles in Reputable National Journals. (Indexed by Sinta), Copyright of the POC Making Module, videos of service implementation, and news in the mass media.